Application Of Web-Based Industrial Environment Test Results - Muhammad Jamilul Iman; Mochamad Alfan Rosid (Universitas Muhammadiyah Sidoarjo, 2021)
Tests on an industrial environment is needed to ensure the health and as a way to combat pollution in the surrounding environment. To obtain data and information about the content of chemical substances that exist in the region need of good accuracy in order to provide accurate research results. If the process using the manual method, it will take a long time to make a report of the information obtained. As for the various samples taken have different standards or methods based on government regulations. The application for processing the results of industrial environment test uses the PHP programming language and uses a MySQL database. Application uses the Black Box method from display to input action. Moreover,testing this application using a Likert scale, the author gives a questionnaire to the marketing of 5 people and laboratory 5 people with questions about the appearance results of input and output application with 5 items. The results of this test, the application of industrial environmental results can be accepted by laboratory application with a percentage of 74.4%. This laboratory application helps data management and administration PT. Xyz, becomes temporary information or the final report on the evaluation of research conducted.